2018
DOI: 10.1038/s41431-018-0148-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional missense and splicing variants in the retinoic acid catabolizing enzyme CYP26C1 in idiopathic short stature

Abstract: Height is a complex quantitative trait with a high heritability. Short stature is diagnosed when height is significantly below the average of the general population for that person's age and sex. We have recently found that the retinoic acid degrading enzyme CYP26C1 modifies SHOX deficiency phenotypes toward more severe clinical manifestations. Here, we asked whether damaging variants in CYP26C1 alone could lead to short stature. We performed exome and Sanger sequencing to analyze 856 individuals with short st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…CYP26C1 is a genetic modifier of SHOX deficiency and downregulates shox expression in zebrafish ( Montalbano et al, 2016 ). Moreover, CYP26C1 variants cause isolated short stature in the absence of SHOX deficiency ( Montalbano et al, 2018 ). Here, we show that shox knockdown significantly upregulates cyp26c1 in zebrafish fins.…”
Section: Discussionmentioning
confidence: 99%
“…CYP26C1 is a genetic modifier of SHOX deficiency and downregulates shox expression in zebrafish ( Montalbano et al, 2016 ). Moreover, CYP26C1 variants cause isolated short stature in the absence of SHOX deficiency ( Montalbano et al, 2018 ). Here, we show that shox knockdown significantly upregulates cyp26c1 in zebrafish fins.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical severity of SHOX pathogenic variants varies even within family members carrying the same variant and damaging mutations of the gene encoding the retinoic acid catabolizing enzyme ( CYP26C1 ) have been reported to act as genetic modifiers of SHOX deficiency ( 44 ). Recently, it was reported that CYP26C1 damaging mutations without SHOX deficiency can also lead to short stature ( 45 ).…”
Section: Defects In Fibronectin-1 Cause Smd-corner Fracture Typementioning
confidence: 99%
“…Missense mutations in CYP26C1 which reduce enzymatic metabolism of RA act as modifiers of missense SHOX mutations conferring the more severe skeletal phenotype of short stature and limb defects (shortening and bowing of the radius together with distal hypoplasia of the ulna and mesomelia) compared to phenotypically normal/mild short stature in family members carrying only the SHOX mutation [223]. It has since been shown that missense mutations and splice variants of CYP26C1 causing reduced enzymatic activity [224]. Homozygote 7 bp duplications leading to a frameshift and a premature stop c.844_851dupCCATGCA p.Glu284fsX128 and/or compound heterozygote mutations of the duplication with an inactivating missense mutation c.1433G > A p.Arg478His give rise to focal facial dermal dysplasia, where an abnormal epidermis and replacement of the dermis by connective tissue and loss of subcutaneous tissues gives rise to skin lesions at the sites of facial fusion during development [225].…”
Section: Cyp26 In Human Genetic Diseasementioning
confidence: 99%